PROFIL KANDUNGAN KIMIA DAN AKTIVITAS ANTIBAKTERI EKSTRAK METANOL DAUN BAMBAN (Donax canniformis (G. Forst.) K. Schum.) TERHADAP Staphylococcus aureus - Hidayatullah Hidayatullah; Syariful Anam; Muhamad Rinaldhi Tandah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2015)
Bamban (Donax canniformis (G. Forst.) K. Schum.) is one of the family Marantaceae plant that has many uses such as traditional medicine. Methanol extract of bamban leaves contains phenolic, tannins and saponins compounds. The purpose of this research is to determine the class of compounds that has antibacterial activity against Staphylococcus aureus and determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) methanol extract of bamban leaves. This extract was prepared using maceration method with methanol solvent. Determination the class of compounds was initiated by bioautografi test in order to determine spots which has have antibacterial activity. Subsequently, the spot were identified the class of compound using reagent spray FeCl3 and H2SO4 10%. The determination of MIC and MBC using dilution method. Research showed there are three compounds that had antibacterial activity. These compounds were predicted as spot I and spot II which were phenolic compounds and spot III as a saponin compound. MIC and MBC value of the methanol extract of leaves bamban leaves 8% and 13%, respectively.